Droppings of Svalbard reindeer (Rangifer tarandus platyrhynchus) as a reservoir of cultivable micromycetes on Spitsbergen - Ogórek, Rafał; Suchodolski, Jakub; Dudek, Bartłomiej (Polish Polar Research, 2022)
Fungi are highly diverse, yet only a minor part of the total estimated species has been cultured and characterized. This might be especially true for Arctic, where studies on the fungal diversity are still scarce. For that reason, our aim was to analyze fungal diversity in the droppings of Rangifer tarandus platyrhynchus. The samples of feces from 32 adult individuals were collected in the southern or central parts of the Wedel Jarlsberg Land (Spitsbergen, Svalbard Archipelago) and assessed for micromycetes diversity using a combination of classical and molecular identification approaches. We found 16 fungal species, out of which three were described as mesophilic, two as psychrotolerant and eleven as psychrophilic. The identified Arctic fungi belonged to eleven genera out of which representatives of Naganishia genus (formerly belonging to Cryptococcus albidus clade) were the most abundant fungal species isolated. Additionally, to our knowledge, we firstly recorded Botrytis cinerea in polar areas. We conclude that droppings of R. tarandus platyrhynchus are a source of different fungal taxa, including fungi potentially pathogenic towards humans, plants and insects.